Gladys Black letter to Thomas H. Kent regarding bird sightings, March 17, 1980 - Black, Gladyset al (1980)
Field notes contributed by Gladys Black in a letter to Thomas H. Kent, March 17, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed